2019
DOI: 10.1080/15548627.2019.1668606
|View full text |Cite
|
Sign up to set email alerts
|

DRD3 (dopamine receptor D3) but not DRD2 activates autophagy through MTORC1 inhibition preserving protein synthesis

Abstract: Growing evidence shows that autophagy is deficient in neurodegenerative and psychiatric diseases, and that its induction may have beneficial effects in these conditions. However, as autophagy shares signaling pathways with cell death and interferes with protein synthesis, prolonged use of autophagy inducers available nowadays is considered unwise. The search for novel autophagy inducers indicates that DRD2 (dopamine receptor 2)-DRD3 ligands may also activate autophagy, though critical aspects of the action mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 92 publications
0
17
0
Order By: Relevance
“…Intriguingly, approaches promoting POS degradation through lysosomes re-acidification within impaired RPE cells include stimulation of beta-2 adrenergic, A2A adenosine, and D5 dopamine receptors [ 118 ]. This is interesting since adenosine, norepinephrine, and dopamine, which play a role in retinal function and POS phagocytosis [ 118 , 119 , 120 , 121 , 122 ], are known to variously affect mTOR-, AMPK-, and TFEB-related autophagy and also the proteasome system through stimulation of beta-adrenergic, A2A adenosine, and D1/D2-like dopamine receptors [ 123 , 124 , 125 , 126 , 127 , 128 , 129 ]. Since autophagy–lysosomal dysfunction associated with either an increased activity of mTORC1 or decreased activity of AMPK or TFEB does predispose to RPE and photoreceptors degeneration in experimental models [ 36 , 97 , 129 , 130 , 131 , 132 ], it would be worth investigating whether a coupling between alterations of autophagy activity and catecholamine innervation occurs in the frame of AMD.…”
Section: Cell-clearing Systems In the Rpe As The Keys For Retinal mentioning
confidence: 99%
“…Intriguingly, approaches promoting POS degradation through lysosomes re-acidification within impaired RPE cells include stimulation of beta-2 adrenergic, A2A adenosine, and D5 dopamine receptors [ 118 ]. This is interesting since adenosine, norepinephrine, and dopamine, which play a role in retinal function and POS phagocytosis [ 118 , 119 , 120 , 121 , 122 ], are known to variously affect mTOR-, AMPK-, and TFEB-related autophagy and also the proteasome system through stimulation of beta-adrenergic, A2A adenosine, and D1/D2-like dopamine receptors [ 123 , 124 , 125 , 126 , 127 , 128 , 129 ]. Since autophagy–lysosomal dysfunction associated with either an increased activity of mTORC1 or decreased activity of AMPK or TFEB does predispose to RPE and photoreceptors degeneration in experimental models [ 36 , 97 , 129 , 130 , 131 , 132 ], it would be worth investigating whether a coupling between alterations of autophagy activity and catecholamine innervation occurs in the frame of AMD.…”
Section: Cell-clearing Systems In the Rpe As The Keys For Retinal mentioning
confidence: 99%
“…O-6-methylguanine-DNA methyltransferase (MGMT) is a type of suicide DNA damage repair enzymes, and DNA damage repair disorders have been reported to induce autophagy (Balvers et al, 2015;Abdu et al, 2020). Lei et al (2020) have found that the high expression of MGMT is significantly correlated with the low expression of ATG4B and the favorable prognosis of gastric cancer.…”
Section: Regulatory Proteins Inhibiting Both Autophagy and Chemoresismentioning
confidence: 99%
“…Under the depletion of nutrients and energy with the increasing AMP/ATP ratio, LKB1 (liver kinase B1), a tumor suppressor kinase, stimulates the activation of AMPK, which subsequently promotes the formation of TSC1/TSC2 complex to inactivate mTORC1 and induce autophagy ( Figure 3 ) ( Bakula et al, 2017 ). Moreover, AMPK can inhibit mTORC1 by directly phosphorylating Raptor ( Barroso-Chinea et al, 2020 ). Under the undernourished condition, AMPK can directly phosphorylate ULK1 at Ser317, S467, S555, S574, S637, and Ser777 by separating mTORC1 from ULK1 and stimulate autophagy ( Zachari and Ganley, 2017 ), whereas mTORC1 can block the function of AMPK by phosphorylating ULK1 under the glucose abundant condition ( Mao and Klionsky, 2011 ).…”
Section: Overview Of Autophagymentioning
confidence: 99%
“…This is associated with neuroprotection and inhibition of alpha-synuclein/SNCA accumulation both in rotenone-treated catecholamine-containing cells that overexpress wild-type or mutant alpha-synuclein and in SNCA transgenic mice ( 76 ). More recently, D3DRs were shown to be specifically responsible for autophagy activation via AMPK stimulation and mTOR inhibition ( 77 ).…”
Section: A Brief View Of the Autophagy Machinery: From Degradation Ofmentioning
confidence: 99%